Analysis of continuity of studies of High School graduates of Uruguaiana schools (Research, Society and Development, 2020)
The approaching end of high school for many students is a time marked by uncertainties, often in view of the student's ignorance of not knowing what to do as a continuation of their studies. This article presents a research investigation with the students of their yearnings, doubts and expectations about doing at the end of their high school. Some alternatives that are presented to concluders students are not studying and working, studying and working, taking a college pre entrance exam course. Studying includes technical or university courses. In order to work on seeking these results, a questionnaire was first designed with closed and open questions. After the questionnaires were applied in schools. Finally, the data were tabulated and some analysis of the students' intentions was made. The survey was conducted in 2016 and repeated in 2017. It was noted a certain convergence of data over the two years to similar results. that is, the university is a search for some students, especially those coming from private school; public school students, if unable to study at Unipampa, tend to go to work and to stay in Uruguaiana.